Welfare reform in the UK: 1997 - 2007 - Mike Brewer (Institute for Fiscal Studies (IFS), 2007)
This paper presents a tour of welfare reform in the UK since the last change of government, summarising the most important changes in active labour market policies, and in measures intended to strengthen financial incentives to work. It argues that developments in the UK's active labour market policies occurred in two broad phases: first, the Government sought to strengthen ALMPs for those individuals deemed to be unemployed, through the New Deal programme. Second, the Government has reformed benefits for individuals traditionally viewed as inactive and thus excused job search activity, such as lone parents, and the sick and disabled. Accompanying these have been changes to direct taxes, tax credits and welfare benefits aiming to strengthen financial work incentives. However, financial work incentives have been strengthened by less than might be expected given the early rhetoric: the expansion in family-based tax credits have weakened the financial work incentives of (potential) second earners in families with children, many more workers now face combined marginal tax and tax credit withdrawal rates in excess of 60% than a decade ago, and a desire to achieve broad reductions in relative child poverty has led the Government to increase substantially income available to non-working families with children. We also summarise evaluations of three important UK welfare-to-work reforms (WFTC, NDYP and Pathways to Work), but without comparing their efficacy.
Keywords: 330; Sozialhilfe; Reform; Familienpolitik; Leistungsanreiz; Arbeitsangebot; Großbritannien